THE EFFECTS OF ACTIVE LABOUR MARKET PROGRAMMES ON UNEMPLOYMENT DURATION - Laužadytė, Agnė (Ekonomika, 2010)
This study estimates the effects of Active Labour Market Programmes on unemployment insurance (UI) benefit recipients in Denmark, depending on the time spent in unemployment before entry into the programme. I estimate two separate effects of the ALMPs in the duration model: a locking-in effect and a post-programme effect, and finally, the net effects of ALMPs on unemployment duration are calculated.The results in this study are in line with the findings of studies in other countries, i.e. I find that only one of ALMP types – Private Job training – reduces unemployment duration. Analysis leads to a conclusion in favour of activation of unemployed persons in their first year of unemployment; however, it does not support activation in the first 1–6 months of UI benefit spells.